Tramadol Hydrochloride in postoperative analgesia: Clinical comparison with Diclofenac sodium - Zahid Ahmad Hashmi; Ghazala Bashir; Shakeel Ahmad Shah (Gomal Journal of Medical Sciences, 2004)
Objective: To compare the effectiveness, duration and side effects of Tramadol Hydrocloride with Diclofenac sodium in the first postoperative twenty-four hours.Setting: District Headquarter Teaching Hospital, D.I. Khan.